Financial Toxicity in Craniofacial Surgery: A Scoping Review of Patient-Level Direct and Indirect Costs - Ravi Dhawan; Gabriella Glassman; Alexandra Boric; Amelia Fogle; Renée Roberts; Ambika Menon; Orr Shauly; Kendall Brooks; Albert Losken; Colin Brady; Gabriela Del Pilar García Nores (FACE, 2026)
Background: Financial toxicity (FT), the harmful effects of treatment-related financial burden on patients and families, is increasingly recognized in surgical care. Patients with craniofacial conditions may be uniquely vulnerable given the prolonged, iterative and multidisciplinary nature of treatment. However, FT in craniofacial surgery remains inadequately characterized. We conducted the first scoping review to map the scope, measurement, and drivers of FT in craniofacial care. Methods: Five electronic databases (PubMed, Embase, Scopus, Web of Science, and Global Health) were searched from inception through December 1, 2025, following PRISMA guidelines. English-language original research reporting patient-level financial outcomes in craniofacial populations was included. Two authors independently screened records and extracted data. Risk of bias was assessed using validated tools for observational designs. Results: Of 2847 citations identified, 18 studies met inclusion criteria, with a total of 18 224 participants. Most studies (83.3%) were published after 2020, and 72.2% originated from high-income countries. The predominant diagnosis was cleft lip and/or palate (15 studies), and 88.9% enrolled pediatric populations. No study employed a validated FT-specific instrument, and only 2 provided an explicit FT definition. Risk of bias was moderate in 10 (55.6%) and high in 8 studies (44.4%). Cumulative OOPcosts reached $45 140, and lifetime care costs reached $73 398 Canadian Dollars across a median of 148.5 healthcare interactions. Travel and indirect costs were the most frequently measured domain (55.6% of studies). Conclusions: Financial toxicity in craniofacial surgery is substantial but inconsistently measured. Development and validation of specialty-specific FT instruments should be prioritized to enable standardized measurement.